Modeling and evaluating passenger evacuation and risk in blended wing body aircraft using continuous displacement agents - Kun Chen; Xiaotian Wang; Pengfei Li; Jiang Xie (Discover Applied Sciences)
Abstract In the aviation industry, ensuring efficient emergency evacuation procedures remains paramount for passenger safety. This research endeavors to investigate the evacuation efficacy of Blended Wing Body (BWB) aircraft, evaluating their operational efficiency and practicality during emergency situations through the development of a continuous displacement field evacuation model compliant with airworthiness standards. Twelve carefully constructed experiments were conducted to refine the simulation model, enabling a comprehensive evaluation of BWB aircraft evacuation performance across diverse scenarios. The findings suggest commendable evacuation performance of BWB aircraft, underscored by the significant impact of accurate crew guidance on evacuation efficiency. Furthermore, a positive correlation between Operational Performance Standards (OPS) values and evacuation duration underscores the pivotal role of evacuation protocols. Notably, BWB aircraft necessitate special consideration for scenarios involving inaccessible rear exits, unlike conventional aircraft. This study not only illuminates the strengths and limitations of BWB aircraft evacuation protocols but also furnishes actionable insights for regulatory bodies, aircraft manufacturers, and airlines to enhance emergency readiness and passenger safety.